Proof of concept uses biometric identification with legal entity identifiers on trade platform - Beck, Steven (ADB briefs., 2021)
The Legal Entity Identifier (LEI) is a 20-digit standard identifier that helps organizations meet due diligence and know-your-customer requirements, including for small businesses. To strengthen the identification process, biometrics such as facial recognition can be used with the LEI so that parties in a transaction can verify their counterparts are authorized representatives of that entity. The Global Legal Entity Identifier Foundation conducted the proof of concept project with support from ADB.